Effect of extraction process parameters on antifungal peptides from Supermeal worm, Zophobas morio (Fabricius) - Faruck, Mohammad Omer; Yusof, Faridah; Chowdhury, Md. Sazzad Hossien (Faculty of Food Science & Technology, Universiti Putra Malaysia, 2017)
Acidified isopropanol extract of whole body larvae of Zophobas morio (Fabricius), which contains peptides, has been shown to exhibit an inhibitory effect towards fungal growth. The larvae, commonly known as supermeal worm are cheap and easily maintained. To make the extraction even more cost effective, it is pertinent to maximize the extraction yield and to optimize the extraction process. The aim of this study is to use the One-Factor-At-a-Time (OFAT) strategy to determine the maximum values of the process parameters for the extraction of antifungal peptides, where these values can later be used in the experimental design to optimize the extraction process. Based on importance, three parameters were selected, namely, initial homogenization temperature, homogenization time and solid (g) to solvent (ml) ratio. Maximum inhibition to fungal growth was found when the extraction was carried out as follows; using initial homogenization temperature of 4°C, homogenization time of 5 minutes and a solid (g) to solvent (ml) ratio of 3.5:1. The peptide extract displayed different degree of antifungal effect towards four selected fungi, Aspergillus niger, Microsporum canis, Candida albicans and Blastomyces dermatitidsis.